Brucella suis--málo známé zoonotické agens - Bardon, J; Pijácek, M; Harna, J; Bzdil, J; Vyroubalová, S; Skalka, P (Klinicka mikrobiologie a infekcni lekarstvi, 2012)
Brucellosis is a rare but serious bacterial zoonosis. Officially, the Czech Republic is among countries that are free from brucellosis in livestock. In the country, sporadic imported human infections may occur, caused by e.g. Brucella melitensis. In wild hare populations, however, rare cases of infection caused by Brucella suis are still observed, potentially threatening humans. The short communication reports two cases of hare brucellosis in Moravia, Czech Republic, and experiences with isolate identification by the MALDI-TOF method.
Keywords: Česká republika; Brucellosis; zajíci; Zoonoses; Czech Republic; brucelóza; zoonózy; Brucella suis; Male; Animals; mužské pohlaví; zvířata; Hares